Using AHP to evaluate the critical factors on management of Indonesian restaurant - Anggraeni, Ghina; Lin, Chun-Nan; Azizah, Siti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2019)
The restaurant is serving cuisines and beverages generally at high prices with a high level of service. The main objective of this research is to know evaluation of the critical factors on management of Indonesian restaurant. Qualitative methodologies were applied using survey data with questionnaires and interviews with restaurant proprietor and employees. The Analytic Hierarchy Process (AHP) used in this study various questions that help respond to restaurant management decision making. The results of the survey show the most important of critical factors on management of restaurant of Indonesia is the safety and cleanliness of beverages, added value experience of devour, technology, and building strategic alliances. To sum up, the most important of crucial factors on the management of restaurant Indonesia is consumer demand in the safety model management of cleanliness in cuisine. It also external and internal management influence added value in devouring and technology. The model of the management partner is strategic alliances of building